Somalia Security and Justice Public Expenditure Review - World Bank (World Bank, Washington, DC, 2017)
In late 2013, the Ministry of Finance (MoF) of the Federal Government of Somalia (FGS) requested that the World Bank and UNSOM jointly conduct a public expenditure review of the security and justice sectors (SJPER). An SJPER is a tool to assist policy and operational decision-making, analyze tradeoffs, and provide options on critical financially-related issues in defense, as well as criminal justice and policing. Three years later, Somalia is undergoing yet another political transition with the election of a new parliament and ultimately a new president. These steps will augur in a new government in 2017 that will be charged with finalizing some of the key issues around the constitution, including the relationship between the federal state and its federal members, as well as leading the country to democratic elections in 2020. Security and justice issues are hinged to many of these overarching political questions; these are two fundamental ‘public goods’ that are central to the (re)building of the Somali state and the transition from war to peace. In this context, the SJPER is a technical tool to assist the FGS, the federal members, and their international partners in placing these critical security and justice policy questions within a public finance perspective. As a tool, rather than a one-off report, it should be used by the authorities and partners going forward in terms of testing the critical policy questions against the key dimensions studied here, including affordability, efficiency and effectiveness and accountability.